Pinus contorta growth in boreal Sweden as affected by combined lupin treatment and soil scarification - Mattson, Stefan; Bergsten, Urban; Mörling, Tommy (Silva Fennica, 2007)
Effects of combining lupin (Lupinus nootkatensis L.) establishment and soil scarification on stem volume and stem biomass yield of lodgepole pine (Pinus contorta Dougl. var. latifolia Engelm.) were studied on a poor boreal site in Sweden 18 years after plantation. A field randomized block experiment was established with three different scarification techniques (disc trenching, moulding and ploughing) followed by establishment of lupins by either seeds or roots. There were three blocks without and two blocks with lupins. Overall, on average for the three soil scarification techniques, the lupin treatment significantly increased the volume per hectare by 102%.The lupin treatment significantly increased the stem volume per hectare by 236% for mounding and 139% for disc trenching, whereas the 55% increase for ploughing was not significant. The increase in the total stem biomass yield per tree was more pronounced for larger trees; 46% for average trees and 106% for dominant trees. However, there were no significant differences between scarification techniques for the lupin treatment in total stem biomass yield. Over the 18-year period, the increased growth rate following the lupin treatment resulted in a significantly decreased average stem basic wood density (on average 6%) for the sample trees. Because lupin is a nitrogen-fixing plant species, the large increase in tree growth following the lupin treatment was probably an effect of increased amount of nitrogen in the soil. The results indicate that use of lupin is a possible alternative to increase site productivity of lodgepole pine on poor boreal sites.